To convert the linear equation \(2x + 3y = 6\) into slope-intercept form, we need to solve for \(y\).
-
Start with the original equation: \[ 2x + 3y = 6 \]
-
Isolate \(3y\) by subtracting \(2x\) from both sides: \[ 3y = -2x + 6 \]
-
Now, divide everything by \(3\) to solve for \(y\): \[ y = -\frac{2}{3}x + 2 \]
Now that we have \(y\) in terms of \(x\), the slope-intercept form of the equation is: \[ y = mx + b \] where \(m\) is the slope and \(b\) is the y-intercept.
From the equation \(y = -\frac{2}{3}x + 2\):
- The slope \(m = -\frac{2}{3}\)
- The y-intercept \(b = 2\)
If you need to fill in specific boxes based on your question format, they may need to be filled out as follows:
- Slope (m): \(-\frac{2}{3}\)
- y-intercept (b): \(2\)
Please confirm if you need further assistance!